Antimonene-based flexible photodetector. Issue 1 (30th August 2019) - Xiao, Qi; Hu, Chen-Xia; Wu, Hao-Ran; Ren, Yong-Yuan; Li, Xiang-Yang; Yang, Qi-Qi; Dun, Guan-Hua; Huang, Zhi-Peng; Peng, Yong; Yan, Feng; Wang, Qiang; Zhang, Hao-Li
Abstract : An effective solution to scalable exfoliation of large lateral sized antimonene nanosheets is developed. Flexible photodetectors based on hybrid structure of surface modified few layer antimonene exhibited excellent performance. Abstract : Antimonene is an emerging semiconducting two-dimensional (2D) material with various attractive properties, but its applications in optoelectronics have rarely been explored. Herein, we report a highly efficient preparation of few-layered antimonene by a polymer ionic liquid (PIL) assisted liquid-phase exfoliation method, which gives above 20% yield of micrometer sized nanosheets. Stability studies suggested that the presence of water in the solvent significantly accelerated the decomposition of the produced antimonene, while the antimonene dispersed in dry DMF exhibited a very high stability under ambient conditions. For the first time, flexible photodetectors based on a hybrid structure of few layer antimonene nanosheets modified by PIL and CdS quantum dots (QDs) were fabricated, which showed a good responsivity of 10 μA W −1 and on/off ratio of 26.8 under the bias of 1 V. This work demonstrates that PIL assisted liquid-phase exfoliation is a very promising method to achieve highly efficient preparation, preservation, and surface modification of few-layer antimonene, and hence enable the application of antimonene-based 2D materials in optoelectronics.